Internet Gambling Offshore - Cooper, A. author. aut Link
XVII, 201 p.
Keywords: In the aftermath of the financial crisis, Cooper locates the WTO-focused struggle between the US and the very small island state of Antigua on Internet gambling in the wider International Political Economy. He draws connections between gambling and offshore and/or enclave cultures and points out the stigmatization of 'Casino Capitalism'.